EYES ON HYPERTENSION: SEVERE MICROVASCULAR RETINAL DYSFUNCTION IN HYPERTENSIVE PATIENTS FAILING TO ACHIEVE BLOOD PRESSURE TREATMENT TARGETS. (June 2018) - Barthelmes, J.; Nägele, M.P.; Ruschitzka, F.; Flammer, A.J.; Sudano, I.
Abstract : Objective: INTRODUCTION: Endothelial dysfunction is crucial in the development, progression, and prognosis of cardiovascular diseases. Small studies in restricted collectives have pointed toward altered retinal endothelial impairment in uncontrolled essential hypertension. There has been no dedicated study to hypertensive patients to this point in time. It was, thus, the aim of this study to evaluate retinal vessel endothelial function - an easily assessable vasculature - in patients with hypertension and evaluate it against structural and functional gold standards. RATIONALE: To investigate micro- and macrovascular function in hypertensive patients who have not achieved blood pressure (BP) treatment goal. MATERIALS & METHODS: 80 patients with ill-controlled hypertension (median age 69 ± IQR = 15 years, mean systolic BP 150.4 ± SD = 11.4mmHg, diastolic BP 91.1 ± 9.4mmHg) were prospectively recruited. 74 healthy individuals (HC) without any cardiovascular risk factors served as controls (age 56 ± 28 years, systolic BP 122.2 ± SD = 9.9mmHg, diastolic BP 76.2 ± 7.1mmHg). Microvascular retinal endothelial function was measured via dynamic retinal vessel analysis (DVA). This non-invasive technique measures mainly NO-dependent flicker light-induced dilatation of retinal arteries (FID). Other vascular outcome measures include retinal arteriovenous ratio (AVR), flow-mediated dilatation (FMD), and pulse-wave velocity (PWV), as well as analysis (PWA, Augmentation index, aortic blood pressure). To account for imbalanced possible confounders (age, sex, body mass index, LDL cholesterol, and fasting plasma glucose), an inverse probability weighted analysis (propensity score) was employed (R 3.4.3, package CBPS). Generalized linear models were used to test group differences in weighted models. Survey means and robust standard errors are reported for weighted analyses. RESULTS: Arterial retinal vascular function (FID) was significantly impaired in patients with ill controlled hypertension (HTN) compared to HC (mean FID 2.77 ± 0.24% vs. 3.86 ± 0.24 %, p = 0.001). Also, post-flicker constriction was found reduced in HTN (2.77 ± 0.24% vs. 3.86 ± 0.24%, p = 0.046). Static retinal vascular analysis revealed significantly (p = 0.001) lower AVR in HTN (0.818 ± 0.008 vs. 0.854 ± 0.007, p = 0.001). PWV was significantly increased in HTN compared to HC (PWV 7.2 ± 0.2 ms-1 vs. 8.7 ± 0.3 ms-1, p < 0.001), Augmentation index at 75/min heart rate was 22.2% in HC versus 25.3 ± 1.5% in HTN (p = 0.045). PWV correlated negatively with FIDart(r = −0.24, p = 0.003). FMD was reduced (5.66 ± 0.35% vs. 6.23 ± 0.42%) yet not significantly so (p = 0.3). Interestingly, FMD exhibited the often-reported negative correlation with vascular baseline diameter (r = −0.45, p < 0.001) but FID did not exhibit such a correlation (r = −0.02, p = 0.84). 61% of HTN (49/80 patients) received no drug therapy at examination, 3% received 3 or more antihypertensive drugs. Balance for potential confounders was achieved (maximum standardized mean difference 0.18 for LDL; sufficient overlap). Discussion & conclusions: Our results demonstrate profound alterations in microvascular function of patients with hypertension. Whether these results have clinical or prognostic impact needs to be carefully evaluated in further clinical studies.